Occurrence of head rot disease caused by Fusarium verticillioides on Chinese flowering cabbage (Brassica rapa L subsp. parachinensis) in China. (August 2020) - Akram, Waheed; Ahmad, Aqeel; Juxian, Guo; Yasin, Nasim Ahmad; Akbar, Muhammad; Luo, Wenlong; Wu, Tingquan; Wang, Qing; Lu, Meilian; Xie, Dasen; Li, Guihua
Abstract: Chinese flowering cabbage ( Brassica rapa L parachinensis ) is a leafy green vegetable with a crunchy stalk and mainly cultivated in the Guangdong province of China. Between January 2017 and January 2018, a disease with head rot symptoms was observed on B. rapa in some agricultural fields around Lianzhou and Guangzhou cities of Guangdong province, China, at an incidence of approximately 50%. Initial disease symptoms included black scattered lesions on the surfaces of flower buds and adjacent leaves. As the disease progressed, the whole head portion turned into a black rotted mass with scattered white mycelial masses. The isolated pathogen from the infected portion of plant was identified as Fusarium verticillioides (Sacc.) Nirenberg based on the morphological and molecular characterization. The disease incidence rate during artificial inoculation was 100%. To our knowledge, this is the first report of F. verticillioides infections on Chinese flowering cabbage in China. Highlights: A new record of Fusarium verticillioides in China. A head rot disease was seen on Chinese flowering cabbage. F. verticillioides as causal agent of head rot disease on Chinese flowering cabbage .